Distribution and Habitat Specificity of Potentially-Toxic Microcystis across Climate, Land, and Water Use Gradients - Marmen, Sophi; Aharonovich, Dikla; Grossowicz, Michal; Blank, Lior; Yacobi, Yosef Z.; Sher, Daniel J. (Frontiers in Microbiology, 2016)
Toxic cyanobacterial blooms are a growing threat to freshwater bodies worldwide. In order for a toxic bloom to occur, a population of cells with the genetic capacity to produce toxins must be present together with the appropriate environmental conditions. In this study, we investigated the distribution patterns and phylogeny of potentially-toxic Microcystis (indicated by the presence and/or phylogeny of the mcyD and mcyA genes). Samples were collected from the water column of almost sixty water bodies across widely differing gradients of environmental conditions and land use in Israel. Potentially toxic populations were common but not ubiquitous, detected in ~65% of the studied sites. Local environmental factors, including phosphorus and ammonia concentrations and pH, as well as regional conditions such as the distance from built areas and nature reserves, were correlated with the distribution of the mcyD gene. A specific phylogenetic clade of Microcystis, defined using the sequence of the mcyA gene, was preferentially associated with aquaculture facilities but not irrigation reservoirs. Our results reveal important environmental, geospatial, and land use parameters affecting the geographic distribution of toxinogenic Microcystis, suggesting non-random dispersal of these globally abundant toxic cyanobacteria.